2020
DOI: 10.3390/electronics9122106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermal Throttling on Long-Term Visual Inference in a CPU-Based Edge Device

Abstract: Many application scenarios of edge visual inference, e.g., robotics or environmental monitoring, eventually require long periods of continuous operation. In such periods, the processor temperature plays a critical role to keep a prescribed frame rate. Particularly, the heavy computational load of convolutional neural networks (CNNs) may lead to thermal throttling and hence performance degradation in few seconds. In this paper, we report and analyze the long-term performance of 80 different cases resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…With respect to CPU usage in these compact devices, it is necessary to consider if the device would suffer from high-temperature issues. These devices are known to work at high temperatures, and high CPU usage would cause temporary or permanent undesirable effects, such as throttling [ 61 ]. Due to that, CPU temperatures were monitored every half second in order to control any possible risk if the device reaches high CPU temperature.…”
Section: Performance Results Obtainedmentioning
confidence: 99%
“…With respect to CPU usage in these compact devices, it is necessary to consider if the device would suffer from high-temperature issues. These devices are known to work at high temperatures, and high CPU usage would cause temporary or permanent undesirable effects, such as throttling [ 61 ]. Due to that, CPU temperatures were monitored every half second in order to control any possible risk if the device reaches high CPU temperature.…”
Section: Performance Results Obtainedmentioning
confidence: 99%
“…During development, the DeMi team found that using Raspberry Pi's as the payload computers provided an accessible computing interface for software development. However, the Raspberry Pi 3 compute modules used in the payload exhibit strong heating under vacuum conditions, which causes throttling of the communications interfaces 41,42 and needed to be mitigated with software changes and regular power cycles. This throttling effect has been observed during on-orbit operations as well.…”
Section: Discussionmentioning
confidence: 99%
“…Benoit-Cattin et al [11] showed that dynamic active cooling can increase the efficiency of image processing on a Raspberry Pi. Their approach, which used an external fan that was controlled by the Raspberry Pi 4B, increased the image processing throughput.…”
Section: External Managementmentioning
confidence: 99%